Milling of jute fibre reinforced polymer composite using uncoated carbide cutting tool - Mir Akmam Noor Rashid (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Jute fibre reinforced polymer (JFRP) composite has become a great significance in a scope of applications. JFRP is being used in automotive, aircrafts, aerospace and domestic upholstery in industrial sectors as a result of its desirable properties, such as light weight, improved stiffness and rigidity, low thermal expansion and high chemical resistance. In this study, JFRP has been fabricated in different composition 60/40 and 70/30, by using Bangla Tossa grade one jute fabric and matrix material via hands lay-up technique. Here, jute fabric was used as reinforcement and epoxy used as matrix material, this hands lay-up processed composite plates were tested for mechanical test like tensile test, flexural test, impact test according to the ASTM standards. The machining process is like milling, drilling, turning, slotting which is necessary during the component assembling stage. Actually, various complexities arise during machining of Jute Fibre Reinforced Polymer (JFRP) such as poor surface finish, delamination, and tool wear. Thus, the objectives of this research are to determine the significant cutting parameters on JFRP milling that influence on the tool wear, tool life, surface roughness and delamination factor. Solid uncoated carbide cutting tool with diameter of 8.0 mm has been used in the CNC milling machine. A Central Composite Design (CCD) of the Response Surface Methodology (RSM) has been used to design the experimental run and to develop the mathematical model based on the collected data. The designed ranges of cutting parameters are spindle speed (671.573-6328.43 rev/min), feed rate (108.58-391.42 mm/min) and depth of cut (0.79-2.21 mm). Analysis of tool wear and surface roughness are conducted using Nikon Measuring Microscope and Veeco Wyko Optical Profiling System Microscope, respectively. In this study, it has been observed that the longest tool life of 41.6 minutes was achieved at lowest feed rate 108.58 mm/min, a cutting speed 3500 rev/min and depth of cut 1.50 mm. The polished and shiny surfaces of the tool wear area which was caused by the abrasive nature of the jute/epoxy composite. Less tool wear was observed at the lowest spindle speed 671.57 rev/min, a feed rate 250 mm/min and depth of cut 1.50 mm. Tool wear increased with the increase of spindle speed, feed rate and depth of cut. Better tool life was obtained at low spindle speed, depth of cut and feed rate. For the measurement of surface roughness, it was observed that the good surface roughness (smoother) achieved at higher spindle speed but became worse with an increasing of feed rate and depth of cut. Higher spindle speed generates the heat between the cutting tool and work piece and burned the pull out fibre which causes less delamination. It was found that higher spindle speed gives lower delamination. Delamination became higher at higher feed rate 391.42 mm/min and depth of cut 2.21 mm. Based on the developed mathematical model, feed rate was identified as the most significant factors for tool life and delamination factor. Depth of cut has an effect on surface roughness but on tool life and delamination have minor effect. The optimized cutting parameter is at spindle speed, feed rate and depth of cut of 4293.788 rev/min, feed rate 150 mm/min, and depth of cut 1.0 mm. These conditions yield optimum value of tool life, surface roughness, and delamination factor of 28.525 min, 1.188 µm, and 1.09, respectively.